Analisis Perbandingan Rasio Keuangan untuk Mengukur Kinerja Pada PT Charoen Pokhand Indonesia Tbk Tahun 2020-2022 (Jurnal Kendali Akuntansi, 2024)
The research aims to compare and analyze financial performance based on liquidity, solvency and profitability ratios in 2020-2022. Data obtained from the sites bei.go.id and https://cp.co.id. This research uses descriptive techniques for case studies using financial data and calculating certain ratios to assess financial performance. The results show that the current ratio is stated to be good, followed by performance in solvency which measures performance with the debt to equity ratio and debt to asset ratio which proves that the debt to equity ratio is stated to be low with an average value of the ratio of 12%, while the performance in debt to assets the ratio is stated to be better. Furthermore, profitability which is measured using return on assets and net profit margin shows that return on assets is stated to be low as well as net profit margin is stated to be low.